PERSEPSI AUDITOR INTERNAL TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT INTERNAL - Susanti, Weni; Fachruzzaman, Fachruzzaman; Baihaqi, Baihaqi (UNIB Press, 2017)
The research was conducted by purposed to know the effect of competence, independence, objectivity and integrity toward audit quality in inspectorate of Province Bengkulu.Analyzed data obtained from 67 respondents, of which the respondents were auditors in inspectorate of Province Bengkulu. Data used in this research is primary data based on questionnaires. The data were analyzed by multiple regression using SPSS 23.Result of the study shows that competence, independence, objectivity and integrity have a significant effect on audit quality in inspectorate of province Bengkulu, meaning that the increase of competence, independence, objectivity and integrity the improvement of audit quality in inspectorate of province Bengkulu. This study also found that competence, independence, objectivity and integrity simultaneously influence on the audit quality in inspectorate of province Bengkulu. meaning that the increase of competence, independence, objectivity and integrity the improvement of the the audit quality in inspectorate of province Bengkulu.